A meta-learning framework for link prediction algorithm selection based on network structure analysis - Brown, Lienke Marie (Stellenbosch : Stellenbosch University, 2025)
Brown, L. M. 2025. A meta-learning framework for link prediction algorithm selection based on network structure analysis. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/e14dfd36-18cd-4933-8555-fd609c8c1672